Peramalan Penyebaran Jumlah Kasus Covid19 Provinsi Jawa Tengah dengan Metode ARIMA - Rachmawati, Ariska Kurnia (Zeta - Math Journal, 2021)
Covid 19 virus disease (corona virus disease), a name given by WHO for patients with coronavirus infection, was first reported from the city of Wuhan, China at the end of 2018. The spread occurred rapidly and created a new pandemic threat. The purpose of this study was to analyze the development of a pandemic in Indonesia, especially in Central Java province. The method used is ARIMA modeling, to determine the percentage of covid19 developments in Central Java. By using the ARIMA method, the ARIMA model (1,1,1) is obtained as a suitable model for the spread of the number of positive cases of Covid-19. Based on this model, with the results that the number of spread of the number of positive cases can be predicted over the next 10 periods, with the result that the number of spread of the number of cases of the Covid-19 virus has decreased from the ece period.